PENGARUH FAKTOR INFLASI, KURS VALUTA ASING, DAN TINGKAT SUKU BUNGA TERHADAP IHSG - Dwi Susilowati; Nehemya Gienah Rabecca Welang; Nadi Hernadi Moorcy (Universitas Widyatama, 2025)
The Jakarta Composite Index (JCI) is an index that reflects the performance of companies listed on the Indonesia Stock Exchange (IDX). Many factors influence the Jakarta Composite Index, including macroeconomic and microeconomic factors. The purpose of this study was to determine the economic factors, including the inflation rate, the rupiah exchange rate, and interest rates, on the Jakarta Composite Index for the 2020-2024 period. The sample size was 60 companies. The data analysis technique used was multiple linear regression with SPSS. The test results showed that inflation significantly affected the Jakarta Composite Index, while the rupiah exchange rate did not significantly affect the Jakarta Composite Index, and interest rates significantly affected the Jakarta Composite Index.